2020
DOI: 10.1111/bor.12452
|View full text |Cite
|
Sign up to set email alerts
|

Holocene relative shore level changes and Stone Age hunter‐gatherers in Hiiumaa Island, eastern Baltic Sea

Abstract: Holocene relative shore level (RSL) changes and Stone Age palaeogeography of Hiiumaa Island are reconstructed using airborne LiDAR elevation data, sedimentological and archaeological proxies as well as GIS‐based landscape modelling. Altogether, 38 RSL index and limiting points are used in modelling and presented in the current paper. The highest raised shorelines of the Ancylus Lake and Litorina Sea, mapped at the elevations of 47 and 26 m a.s.l., formed around 10.3 and 7.4 cal. ka BP, respectively. The recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The mean elevations of the two highest shorelines which are traceable around the Salme palaeostrait system were calculated based on the methodology which was described by Rosentau et al (2020) and the LiDAR-DTM (Estonian Land Board, 2020). The elevation was measured at every 40–60 m along the shoreline in the respective DTM.…”
Section: Methodsmentioning
confidence: 99%
“…The mean elevations of the two highest shorelines which are traceable around the Salme palaeostrait system were calculated based on the methodology which was described by Rosentau et al (2020) and the LiDAR-DTM (Estonian Land Board, 2020). The elevation was measured at every 40–60 m along the shoreline in the respective DTM.…”
Section: Methodsmentioning
confidence: 99%
“…These publications suggested some fresh ideas for the interpretation of the earlier findings, prompting revision of the Baltic Sea history in the area. It should be emphasised that in discussing the shore-level displacement history, an increasing importance of the underwater landscape studies, including those in submerged archaeological layers, has been demonstrated as well (Veski et al 2005;Žulkus et al 2015;Girininkas, Žulkus 2012Girininkas, Žulkus , 2017Žulkus, Girininkas 2020;Berzins et al 2016;Muru et al 2017;Hansson et al 2018;Nirgi et al 2020;Rosentau et al 2013Rosentau et al , 2020. Correlation between geological-geomorphological and archaeological data is of particular importance analysing the Lateglacial -Early Holocene environmental dynamics in the area and we follow the trend in our study as well.…”
Section: Baltica Volume 34 Number 2 December 2021: 216-245mentioning
confidence: 99%
“…Moreover, in this relatively flat landscape, the elevated dunes would serve as a protective barrier against westerly winds [102,103], creating an environment where people feel secure. Potentially, more bushes and trees could thrive here during the harsh conditions of the Dryas 3 stadial.…”
Section: Archaeological Implications Of the New Landscape Modelmentioning
confidence: 99%